Perilymph Fistula as a Complication of Eustachian Tube Dilation and Tympanoplasty. (7th May 2022) - Kim, R.; Scholtz, L. U.; Jadeed, R.; Pfeiffer, C. J.; Sudhoff, H.; Todt, I.
Abstract : Eustachian tube dilation (ETD) is an established, minimally invasive therapeutic approach for chronic eustachian tube dysfunction. The complications associated with performing a ETD are rare. A 22-year-old female patient presented with chronic otitis media on the right side and chronic obstructive tube dilation disorder on both sides. A type I tympanoplasty was performed on the right side because of a tympanic membrane perforation after a ETD on both sides without apparent complications. On the 5th postoperative day, she presented with headache, dizziness and hearing loss on the right side. There was a decrease of hearing threshold on the right side in the pure-tone audiogram and vHIT, cVEMP, and SVV were irregular. The β -2-transferrin test was positive. Since a right-sided perilymph fistula was suspected, an emergency tympanotomy was performed with a round window membrane cover with fascia on the right side. Intraoperatively, a regular, intact ossicular chain was found with a slightly moist middle ear mucosa. The round window membrane was covered by the promontorial lip. Under these measures, the patient's dizziness regressed. The right ear pure-tone threshold vHIT, cVEMP, and SVV normalized.